PERBANDINGAN PENGUJIAN UNDANG-UNDANG OLEH MAHKAMAH KONSTITUSI INDONESIA DAN CHILE: Comparison Of Judicial Review By The Indonesian and Chilean Constitutional Courts - Natalie Gabriel Musak; Eko Primananda (Reformasi Hukum Trisakti, 2026)
One of the main authorities of the Constitutional Court in various countries is to review laws against the Constitution, including the Constitutional Court of Indonesia and the Constitutional Court of Chile. The mechanism applied by the Indonesian Constitutional Court is Judicial Review, where the law has been passed and promulgated. The Chilean Constitutional Court, on the other hand, uses Judicial Preview, meaning the law has not yet been passed and is still in draft form. This article explores the similarities and differences in the constitutional review mechanisms of both courts. The research adopts a normative legal method with a comparative approach, using secondary data obtained through literature study. The data is analyzed qualitatively, and conclusions are drawn through deductive reasoning. The results and conclusion of this article show that the Constitutional Court of Indonesia and the Constitutional Court of Chile share one of the same main authorities, namely the review of laws, which is regulated in accordance with each country's legal system. In addition, the Constitutional Courts of Indonesia and Chile have several differences in terms of authority, the mechanism of law review, and the model of constitutional review.